Lexicon of Argead Makedonia - Heckel, Waldemar (Frank & Timme, 2020)
Intro -- Contents -- Contents -- Introduction -- Frequently cited literature -- Abbreviations -- Argead rulers -- List of contributors -- Acclamation -- Achaimenids -- Achilles -- Aegean -- Aëropos II -- Agriculture -- Aigai -- Aischines -- Aleuads -- Alexander historiographers -- Alexander I -- Alexander II -- Alexander III -- Alexander III, medieval reception -- Alexander IV -- Greek -- Alexandreia -- Amazons -- Ammon, Zeus-Ammon -- Amphipolis -- Amyntas I -- Amyntas II -- Amyntas III -- Amyntas, son of Perdikkas III -- Animal scalps on coins -- Anthemous -- Antigonos Monophthalmos -- Antipatros -- Apollon -- Archelaos -- Archelaos, founder hero -- Argeads, proto-historical -- Argeads, terminology ( -- Argos, Peloponnese -- Aristoboulos -- Aristotle -- Army Assembly -- Army organization -- Arrhidaios (Philip III) -- Art, Makedonian -- Asia Minor -- Athena -- Athens -- Attalos -- Babylon -- Baktrian-Sogdian revolt -- Beards, beardlessness -- Bematists -- Bessos (Artaxerxes V) -- Bisaltia -- Boar, wild boar -- Boiotia -- Boukephalos -- Branchidai -- Burial -- Calendar, Makedonian -- Chaironeia, battle of -- Chalkidians -- Chares of Mytilene -- City-foundations -- Coin hoards -- Coin hoards (bronze) from Eastern Makedonia: "Drama" (DH) and "East Makedonia" (EMH) -- Coinage, Argead -- Comedy, Greek -- Conspiracies, against Argeads -- Court -- Crocus Field, battle of -- Deities -- Delphic Amphiktyony -- Demetrios Poliorketes -- Demochares -- Demosthenes -- Dion -- Dionysios I and Dionysios II of Syrakousai -- Dionysos -- Douris of Samos -- Dynastic Image -- Eagle, on coins -- Education, Makedonian -- Egypt -- Elephant, war elephant -- Elimeia -- Eordaia -- Epeiros -- Ephippos of Olynthos -- Euboulos -- Eumenes of Kardia -- Euripides -- Eurydike, wife of Amyntas III -- Exiles' Decree -- Factions -- Fleet -- Foundation myth.